POPULATION OF ISSYK-KUL REGION: TRADITIONAL SETTLEMENT AND CURRENT STATE (BASED ON MATERIALS OF AN INTERNATIONAL ETHNOGRAPHIC EXPEDITION) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is written on the materials of an international ethnographic expedition to the Issyk-Kul region from September 14 to 24, 2021. The author’s research focuses on the problems of the historical settlement of the titular nation and the newcomer population.
Keywords: ethnic groups and subgroups, ethnic groups, manaschi, storytellers.